Supplementation of Jengkol Peel on VFA Molar Proportion, Methane Production, and Hydrogen Balance in Vitro - N. Hidayah; Nurhaita Nurhaita; R. Zurina (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2020)
This research was designed to study about effects of supplementation jengkol (Archidendron jiringa) peel powder on VFA molar proportion, production of methane, and hydrogen balance in vitro. The experiment used randomized block design with 4 treatments (0%, 2%, 4%, 6%) and 4 replications. The research observed of VFA molar proportion, production of methane, and hydrogen balance. Data were analyzed using Analysis of Variance (ANOVA), and the Duncan Multiple Range Test examined the differences among treatment means. The results showed that the supplementation of jengkol (A. jiringa) peel powder until 6% did not affect (P>0.05) VFA molar proportion but the treatment without supplementation of jengkol (A. jiringa) peel powder had the highest (P<0.05) methane and H2 production. It was concluded that the supplementation of jengkol (A. jiringa) peel powder until 6% decreased methane and hydrogen production but did not affect on VFA molar proportion.